A personality-based surveillance model for Facebook apps - Van der Schyff, Karl Izak (Rhodes University, Faculty of Commerce, Department of Information Systems, 2020)
The surveillance of data through the use of Facebook Apps is an ongoing and persistent problem that impacts millions of users. Nonetheless, limited research has been conducted investigating to what extent a Facebook user's personality influences their awareness of such surveillance practices. Thus, to understand this situation better, the current study inductively developed four propositions from secondary data sources as part of a detailed content analysis. Spanning three search and analysis phases the content analysis led to the development of the research model. Guided by the propositions and research questions, a questionnaire was developed based on the relevant constructs prescribed by the Theory of Planned Behaviour. This questionnaire was used, and a total of 651 responses were collected from Facebook users over the age of 18 years old and residing in the United States of America. Primary data took place at both a univariate and multivariate level with a specific focus on the development of a structural model. Interpretation of the structural model revealed that out of all the Big Five personality traits, Conscientiousness exhibited the strongest relationship with information security awareness followed by Openness to Experience and Neuroticism, respectively. The results further indicated that the model constructs based on attitude, social norms and awareness significantly influenced the intended use of Facebook Apps. The study also contributes by indicating which personality traits are most vulnerable to Facebook App surveillance. For example, it was found that individuals high in Conscientiousness are the least vulnerable with individuals high in Extraversion being the most vulnerable. Since the results indicate that not all the personality traits are significantly related to the model constructs, additional factors may contribute to App surveillance in this context. Concerning this, factors such as user apathy, information privacy, privacy concerns, control and Facebook dependency are discussed as a means to argue why this might be the case.
Keywords: Facebook (Electronic resource); Electronic surveillance -- Psychological aspects; Online social networks -- Psychological aspects; Social media -- Psychological aspects; Personality